2002
DOI: 10.1124/mol.62.3.672
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Phospholipase Cγ2 by Tyrosine Phosphorylation

Abstract: Phospholipase C␥2 (PLC␥2) has been implicated in collageninduced signal transduction in platelets and antigen-dependent signaling in B-lymphocytes. It has been suggested that tyrosine kinases activate PLC␥2. We expressed the full-length cDNA for human PLC␥2 in bacteria and purified the recombinant enzyme. The recombinant enzyme was Ca 2ϩ -dependent with optimal activity in the range of 1 to 10 M Ca 2ϩ . In vitro phosphorylation experiments with recombinant PLC␥2 and recombinant Lck, Fyn, and Lyn tyrosine kinas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 36 publications
4
41
0
Order By: Relevance
“…In contrast, thrombin and 2-MeS-ADP, as expected, had no or only weak effects on LAT tyrosine phosphorylation. However, and in consequence, we found that Pam3CSK4 promoted marked PLC2 phosphorylation at Tyr759 residues, the latter which has been reported to be associated with human platelet activation in response to collagen [36].…”
Section: Platelet Activation Induced By Thrombin Via Pars or Collagensupporting
confidence: 55%
“…In contrast, thrombin and 2-MeS-ADP, as expected, had no or only weak effects on LAT tyrosine phosphorylation. However, and in consequence, we found that Pam3CSK4 promoted marked PLC2 phosphorylation at Tyr759 residues, the latter which has been reported to be associated with human platelet activation in response to collagen [36].…”
Section: Platelet Activation Induced By Thrombin Via Pars or Collagensupporting
confidence: 55%
“…Phospholipase C gamma-2 (PLCγ-2) has been implicated in collagen-induced signal transduction in platelets and antigen-dependent signaling in B-lymphocytes (Ozdener et al, 2002) Our results show an increase in the phosphorylation of PLCγ-2 on Tyr 759 site, following treatment with PPD and stimulation with low doses of collagen, suggesting the involvement of PPD in platelet activation.…”
Section: Discussionmentioning
confidence: 58%
“…7B). PLC␥ 1 is universally expressed in most tissues (46), whereas PLC␥ 2 is an inducible isoform (35). Strong expression of PLC␥ 1 (140 kDa) appeared in RA-ECs and a much weaker signal was detected in RASMCs (Fig.…”
Section: Effects Of Plc Pathway Inhibitors On Vascular Activity In Ramentioning
confidence: 93%